A Study of Conscious Sedation with Ketamine–Propofol for Closed Reduction in Closed Fracture Forearm and Leg - Chanthathamrongwat, Thachapol; Apiwatchatchawan, Chotima; Nopsri, Patcharida; Tipyotha, Suphalak; Intarungsee, Kannika (Medical Journal of Sakon Nakhon Hospital, 2024)
The objective of this study was to evaluate the effectiveness of conscious sedation with Ketamine–Propofol for closed reduction in 90 patients aged 3 – 70 years who presented with closed fracture forearm and leg, and required sedation for closed reduction by Orthopedists at operating room, Sakon Nakhon hospital. They were received 1 microgram/kilogram of Fentanyl, 0.5 milligram/ kilogram of Ketamine and 1 milligram/kilogram of Propofol. The time intervals were measured from drug administration to reduction, awake, recovery and fulfill the criteria for discharge from a recovery room. The results showed that the closed reduction was successfully performed in 90 patients (100%). The average time intervals from drug administration to reduction, awake and first purposeful response and to safety discharge from recovery room were 3, 11.14 and 31.67 minutes, respectively. Patients were breathing spontaneously during the maneuver without any complication. Moreover, they were easy to awake and had adequate ventilation, fast recovery, no pain and no hemodynamic change. The only complication, which is nausea/vomiting, was found in 3 patients (3.33%) and could be treated by medication without repeated symptom. In conclusion, conscious sedation with Ketamine together with Propofol is efficient and effective for patients who underwent closed reduction in closed fracture forearm and leg in terms of safety and fast recovery.